Kejayaan dan Kemunduran Islam pada Masa Dinasti Abbasiyah - Arif Muzayin Shofwan (Jurnal Keislaman, 2026)
Civilizations of all nations, anywhere and at any time, can experience periods of glory, decline, and even destruction. The Abbasid Caliphate in Baghdad was the largest government in the history of Islamic civilization, ultimately experiencing its downfall. Of course, any civilization, no matter how large, can experience destruction. This qualitative descriptive study, using literature review, will discuss the glory and decline of the Abbasid Caliphate. The data analysis technique uses content analysis, sorting data according to the objectives and research problems. This paper yields two results: First, the glory of the Abbasid Caliphate during the periodic rule of the seven caliphs: Caliph Al-Mansur, Caliph Al-Mahdi, Caliph Harun Al-Rashid, Caliph Al-Ma'mun, Caliph Al-Mu'tasim, Caliph Al-Watsiq, and Caliph Al-Mutawakkil. Second, the decline of the Caliphate of the Abbasid Dynasty began to appear during the time of Caliph Al-Mutawakkil and the establishment of the Caliphate of the Bani Buwaihiyah Dynasty and the arrival of the Seljuqs in Baghdad. In the end, the Abbasid dynasty was completely destroyed when Baghdad moved into the hands of the Mongols led by Hulagu Khan during the time of Caliph Al-Mu'tasim.